DESAIN KEMASAN MAKANAN TRADISIONAL MADURA DALAM RANGKA PENGEMBANGAN IKM - Iffan Maflahah (Agroindustrial Technology, University of Trunojoyo Madura, 2012)
Packages are denoting an attributeof a product, it canbe informationmedia andaffect the image the brandofproduct. Designan attractiveproduct packagingwillbeidentity anddistinctive characteristics, that canbe used asthe consumer appeal. Productpackaging designof Unit Kecil dan Menengah (UKM) as produce traditional foodis verysimpleand less attractive. The purposeof this research isto designa Madura’s traditionalfood packaging to promote UKM. Madura’straditionalfoodpackaging designis usingthe samepackaging, the differences onlydistinguishableon the outside ofthe packaging of products. The sharp model of packages arepaper bags andcardboardbox packaging. The image which put on the packages areusing Jembatan Suramadu as iconsofMadura Island